Latest Updates on Lipid Management - Egom, Emmanuel Eroume-A; Pharithi, Rebabonye B; Hesse, Soressa; Starr, Neasa; Armstrong, Richard; Sulaiman, Habitha Mohammed; Gazdikova, Katarina; Mozos, Ioana; Caprnda, Martin; Kubatka, Peter; Kruzliak, Peter; Khan, Barkat; et al. (High blood pressure & cardiovascular prevention, 2019)
Atherosclerotic cardiovascular disease (ASCVD) is the leading cause of death worldwide. Despite the clinical long-term and near-term benefits of lowering cholesterol in, respectively, primary and secondary prevention of ASCVD, cholesterol levels remain under-treated, with many patients not achieving their recommended targets. The present article will review the latest updates on lipid management with emphases on the different classes of cholesterol-lowering agents and their clinical uses.
Keywords: anticholesteremika; Triglycerides; ochranné faktory; chování snižující riziko; cvičení; Protective Factors; výsledek terapie; ateroskleróza; Risk Reduction Behavior; Cholesterol; Atherosclerosis; dyslipidemie; Anticholesteremic Agents; Humans; biologické markery; triglyceridy; ASCVD; Atherosclerotic cardiovascular disease; zdravá strava; rizikové faktory; Exercise; Lipid management; Biomarkers; Diet, Healthy; Risk Factors; Treatment Outcome; Dyslipidemias; lidé; cholesterol